2021
DOI: 10.1002/dad2.12178
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal dementia subtypes based on behavioral inhibition deficits

Abstract: Introduction We aimed to investigate phenotypic heterogeneity in the behavioral variant of frontotemporal dementia (bvFTD) through assessment of inhibition deficits. Methods We assessed occurrences of 16 behavioral inhibition deficits from video recordings of 15 bvFTD patients (early stage) and 15 healthy controls (HC) in an ecological setting. We extracted dimensions of inhibition deficit and analyzed their correlations with cognitive and clinical measures. Using these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…The data gathered for this article are part of the ECOCAPTURE protocol (Clinicaltrials.gov:NCT02496312; see Batrancourt et al (Batrancourt et al 2019) and Supplementary file 1 Part A for further details on this protocol) designed to investigate the behavioral signature and mechanisms of neuropsychiatric syndromes such as apathy or disinhibition (Godefroy et al 2021). For this study, we used data allowing to investigate the behavioral signature and mechanisms of apathy: behavioral measures collected with an ecological approach, clinical measures of apathy (by questionnaires) and MRI data.…”
Section: Participants and Protocol Overviewmentioning
confidence: 99%
“…The data gathered for this article are part of the ECOCAPTURE protocol (Clinicaltrials.gov:NCT02496312; see Batrancourt et al (Batrancourt et al 2019) and Supplementary file 1 Part A for further details on this protocol) designed to investigate the behavioral signature and mechanisms of neuropsychiatric syndromes such as apathy or disinhibition (Godefroy et al 2021). For this study, we used data allowing to investigate the behavioral signature and mechanisms of apathy: behavioral measures collected with an ecological approach, clinical measures of apathy (by questionnaires) and MRI data.…”
Section: Participants and Protocol Overviewmentioning
confidence: 99%
“…Taking these limitations and considerations into account, we recently proposed a behavioural study using an ecological paradigm mimicking a real-life situation, under controlled conditions and a structured scenario (ECOCAPTURE, FRONTlab, ICM), to identify objectively and quantify behavioural disorders, such as apathy and disinhibition ( Batrancourt et al, 2019 , Godefroy et al, 2021 ). We have previously proposed a precise description of behavioural disinhibition in bvFTD based on the literature review ( Paholpak et al, 2016 , Rascovsky et al, 20112011 , Snowden et al, 2001 ) which involves a list of 16 behaviours of interest potentially observable in the context of the ECOCAPTURE scenario.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously proposed a precise description of behavioural disinhibition in bvFTD based on the literature review ( Paholpak et al, 2016 , Rascovsky et al, 20112011 , Snowden et al, 2001 ) which involves a list of 16 behaviours of interest potentially observable in the context of the ECOCAPTURE scenario. In this previous study, we distinguished three disinhibition categories: compulsivity , impulsivity and social disinhibition ( Godefroy et al, 2021 ). We found that a bivariate model fit the data from our bvFTD patients well, defining a two-dimensional structure for the classification of behaviours related to inhibition deficits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations